2018
DOI: 10.1111/cge.13474
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for in‐person disclosure: Patients declining telephone disclosure characteristics and outcomes in the multicenter Communication Of GENetic Test Results by Telephone study

Abstract: Telephone disclosure of cancer genetic test results is noninferior to in‐person disclosure. However, how patients who prefer in‐person communication of results differ from those who agree to telephone disclosure is unclear but important when considering delivery models for genetic medicine. Patients undergoing cancer genetic testing were recruited to a multicenter, randomized, noninferiority trial (NCT01736345) comparing telephone to in‐person disclosure of genetic test results. We evaluated preferences for in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…In a survey of 339 individuals who underwent BRCA testing, O'Shea and colleagues [31] found that participants perceived that face-to-face results disclosure facilitated information exchange and provision of emotional support. Likewise, Beri and colleagues [32] evaluated factors associated with preference for inperson result disclosure. They found that individuals who opted for in-person disclosure were more likely to be older and more likely to be undergoing multigene panel testing.…”
Section: Discussionmentioning
confidence: 99%
“…In a survey of 339 individuals who underwent BRCA testing, O'Shea and colleagues [31] found that participants perceived that face-to-face results disclosure facilitated information exchange and provision of emotional support. Likewise, Beri and colleagues [32] evaluated factors associated with preference for inperson result disclosure. They found that individuals who opted for in-person disclosure were more likely to be older and more likely to be undergoing multigene panel testing.…”
Section: Discussionmentioning
confidence: 99%
“…Patient recruitment is limited to Level I trauma centers capturing a more urbanized population, and thus our findings cannot be extrapolated to all mTBI patients. Proportions of telephone vs. in-person follow-ups, which have been shown to influence extent of disclosure in cancer and genetics studies (42), were unavailable from our dataset and constitutes another limitation. This is a study of association, hence we are unable to make claims regarding causality or pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…This reluctance is not consistent with other studies, such as the one carried out in a US population, where the majority of patients (82%) agreed to be randomized to in-person versus telephone-based results visits. 17 Cultural background and physical proximity to the public health-care system may explain these differences.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to substantial physical distance, traditional predictors of non-in-person visits were age and disclosure of multiplex panel testing results. 17 In our work, we hypothesized that other individual features, such as the personality traits of the person undergoing germline genetic testing, could be relevant in predicting the acceptance of non-in-person visits.…”
Section: Discussionmentioning
confidence: 99%